Strategies, Challenges, and Solutions for Learning Islamic Religious Education for Children with Mental Disabilities SLBN Lampung Province - Puspita Sari, Nina Ayu; Idi, Abdullah; Astrid, Annisa (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study aims to analyze the learning strategies, challenges faced, and solutions implemented by teachers in teaching Islamic Religious Education (PAI) to students with mild intellectual disabilities at SLBN PKK, Lampung Province, and SLB Dharma Bakti Dharma Pertiwi, Bandar Lampung City. This research uses a qualitative approach with a multisite type, employing data collection techniques such as observation, in-depth interviews with PAI teachers, and documentation of learning activities. The collected data were then analyzed descriptively and qualitatively through data reduction, data presentation, and drawing conclusions. The results show that PAI learning strategies at SLBN PKK, Lampung Province, and SLB Dharma Bakti Dharma Pertiwi, Bandar Lampung City, emphasize an individual approach, simple methods, direct practice, and habituation of religious rituals to facilitate student understanding. The challenges faced include students' limited cognitive abilities, a lack of engaging learning media, and low parental involvement. To address these issues, teachers applied solutions such as modifying teaching methods, using simple media, adopting a personal approach, and collaborating with parents to reinforce religious values at home. The study concludes that the success of PAI learning for students with mild intellectual disabilities requires adaptive strategies, contextualized media, and synergy between teachers, schools, and families to achieve the goals of religious education optimally.